2012
DOI: 10.1038/ni.2426
|View full text |Cite|
|
Sign up to set email alerts
|

The p110δ isoform of the kinase PI(3)K controls the subcellular compartmentalization of TLR4 signaling and protects from endotoxic shock

Abstract: Lipopolysaccharide activates plasma-membrane signaling and endosomal signaling by Toll-like receptor 4 (TLR4) through the TIRAP-MyD88 and TRAM-TRIF adaptor complexes, respectively, but it is unclear how the signaling switch between these cell compartments is coordinated. In dendritic cells, we found that the p110δ isoform of phosphatidylinositol-3-OH kinase (PI(3)K) induced internalization of TLR4 and dissociation of TIRAP from the plasma membrane, followed by calpain-mediated degradation of TIRAP. Accordingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
207
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(234 citation statements)
references
References 62 publications
23
207
3
1
Order By: Relevance
“…Thus, this data supports the requirement of hydrophobic contacts, such as the acyl chains of the lipid, for binding. TIRAP PBM binding to PtdIns(4,5)P 2 -enriched liposomes was with nanomolar affinity and displayed sigmoidal kinetics, resembling the binding traces reported for TIRAP 13 . Similar sets of NMR resonance perturbations of TIRAP PBM were also observed in the presence of PtdIns(3)P, emphasizing the promiscuity of the PI binding site of TIRAP.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Thus, this data supports the requirement of hydrophobic contacts, such as the acyl chains of the lipid, for binding. TIRAP PBM binding to PtdIns(4,5)P 2 -enriched liposomes was with nanomolar affinity and displayed sigmoidal kinetics, resembling the binding traces reported for TIRAP 13 . Similar sets of NMR resonance perturbations of TIRAP PBM were also observed in the presence of PtdIns(3)P, emphasizing the promiscuity of the PI binding site of TIRAP.…”
Section: Discussionsupporting
confidence: 63%
“…Membrane binding of TIRAP is regulated by phosphatidylinositol-5 kinase (PI5K), an enzyme that generates intracellular PtdIns(4,5)P 2 and co-localizes with TIRAP at the plasma membrane 12 . Moreover, TIRAP interacts with PI3Ks, enzymes that convert PtdIns(4,5)P 2 into PtdIns(3,4,5)P 3 , impairing TIRAP's membrane targeting 13 . The activity of TIRAP upon TLR2 and TLR4 activation is tightly regulated by sequential events of phosphorylation and ubiquitination.…”
mentioning
confidence: 99%
“…The small GTPase ADP-ribosylation factor 6 also regulates transport of the TLR4 adaptor TIRAP and TICAM-2 to distinct signaling platforms (33). In addition, multiple molecules such as CD14, MD-2, PI3K, and Raftlin regulate TLR4 internalization (16,17,31), which is important in shifting the TLR4 signaling axis from MyD88 to TICAM-1, leading to expression of IFN-b and IFNstimulated genes including caspase 4/11, a cytoplasmic LPS receptor (34,35). Hence LPS-induced dynamic redistribution and intracellular trafficking of TLR4 and its adaptor molecules control innate immune signaling against microbial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane-bound CD14 mediates the LPS-induced endocytosis of TLR4 and the tyrosine kinase Syk regulates this process (16). Moreover, the p110d isoform of PI3K acts as a regulator of TLR4 endocytosis in dendritic cells (DCs) through modulating phosphatidylinositol-(4, 5)-bisphosphate metabolism (17). However, the precise molecular mechanisms that control the translocation of LPS-TLR4 and spatiotemporal regulation of TLR4-mediated signaling are still unknown.…”
mentioning
confidence: 99%
“…It has been shown that phosphatidylinositol 4,5-bisphosphate [PI(4,5)P 2 ] and its derivatives are vital for TLR4 signaling (Kagan and Medzhitov, 2006;Aksoy et al, 2012). PI(4,5)P 2 is confined almost exclusively to the inner leaflet of the plasma membrane and is generated mainly by phosphorylation of phosphatidylinositol 4-monophosphate [PI(4)P] catalyzed by type-I phosphatidylinositol 4-phosphate 5-kinase (PIP5K) isoforms Iα, Iβ and Iγ (encoded in humans by PIP5K1A, PIP5K1B and PIP5K1C, respectively) (Kunz et al, 2000).…”
Section: Introductionmentioning
confidence: 99%